Austerity - Yanis Varoufakis (London Vintage Digital, 2018)
Yanis Varoufakis is the former finance minister of Greece and the author of several international bestselling books. And the Weak Suffer What They Must?: Europe, Austerity and the Threat to Global Stability reveals the underlying problems that led to the Eurozone crisis and its ongoing catastrophic mishandling. Adults In the Room: My Battle with Europe's Deep Establishment is an explosive memoir that reveals what goes on behind the scenes in Europe's corridors of power. Talking To My Daughter About the Economy: A Brief History of Capitalism (forthcoming) explains through vivid stories and easily graspable concepts what economics actually is and why it is so dangerous in the form of a letter to his teenage daughter.
Keywords: Finance, Public; Economic policy